A machine learning approach for virtual screening of histone deacetylase inhibitor compounds using aromatic signatures - Cioletti, Alessandra Gomes; Mariano, Diego; de Melo-Minardi, Raquel Cardoso (Anais do Simpósio Brasileiro de Bioinformática (BSB), 2025)
This work presents a machine learning approach for the virtual screening of histone deacetylase (HDAC) inhibitors, with a focus on the HDAC1 enzyme. Proposing a new structural signature based on the aromaticity of ligand atoms, the method models the protein-ligand binding region as a graph. Machine learning models were trained using this signature to distinguish ligands from decoys, achieving high accuracy. The methodology was applied to identify potential HDAC1 inhibitors from the T3DB database, resulting in the selection of compounds with binding potential. The results suggest that structural signatures are more efficient and computationally less expensive than molecular docking, thereby paving the way for the identification of HDAC inhibitors relevant to autism etiology studies.